Innate-like T lymphocytes in chronic liver disease - Papanastasatou, Maria; Verykokakis, Mihalis (Frontiers in Immunology, 2023)
In addition to its metabolic activities, it is now clear that the liver hosts a number of diverse immune cell types that control tissue homeostasis. Foremost among these are innate-like T lymphocytes, including natural killer T (NKT) and mucosal-associated innate T (MAIT) cells, which are a population of specialized T cells with innate characteristics that express semi-invariant T cell receptors with non-peptide antigen specificity. As primary liver residents, innate-like T cells have been associated with immune tolerance in the liver, but also with a number of hepatic diseases. Here, we focus on the biology of NKT and MAIT cells and how they operate during the course of chronic inflammatory diseases that eventually lead to hepatocellular carcinoma.